2014
DOI: 10.1021/ic501308q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of the Electron-Poor II–V Semiconductor ZnAs

Abstract: ZnAs was synthesized at 6 GPa and 1273 K utilizing multianvil high-pressure techniques and structurally characterized by single-crystal and powder X-ray diffraction (space group Pbca (No. 61), a = 5.6768(2) Å, b = 7.2796(2) Å, c = 7.5593(2) Å, Z = 8). The compound is isostructural to ZnSb (CdSb type) and displays multicenter bonded rhomboid rings Zn2As2, which are connected to each other by classical two-center, two-electron bonds. At ambient pressure ZnAs is metastable with respect to Zn3As2 and ZnAs2. When h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…These trends are also observed in ZnAs as it shows [23] a dominant thermal expansion along a, and similar thermal variation of the Zn-As intra-ring distances and Zn-distances. The large anisotropy of the thermal expansion, and especially the large expansion along the a-direction, is linked to the strong deformation of the Zn 2 Sb 2 rings.…”
Section: Computational Detailssupporting
confidence: 68%
See 2 more Smart Citations
“…These trends are also observed in ZnAs as it shows [23] a dominant thermal expansion along a, and similar thermal variation of the Zn-As intra-ring distances and Zn-distances. The large anisotropy of the thermal expansion, and especially the large expansion along the a-direction, is linked to the strong deformation of the Zn 2 Sb 2 rings.…”
Section: Computational Detailssupporting
confidence: 68%
“…In a very recent study, Fischer et al [23] also found highly anisotropic thermal expansion in ZnAs with the b and c-lattice parameters decreasing with increasing temperature. Nevertheless, these observations still need to be conrmed both experimentally and theoretically.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…ZnSb, thereby, has been classified as an electron-poor framework semiconductor (EPFS) [26,31]. A quite similar interpretation for the structure has been applied to the related compounds CdSb [30,[32][33][34] and ZnAs [35].…”
Section: Crystallographic Structure and Covalent Bondsmentioning
confidence: 99%
“…The most common ones are cold-pressing (at room temperature with ultra-pressure 2-10GPa [83,91]), hot-pressing (>450°C with pressure of 20-300MPa [16,19,20,35]), and spark plasma sintering (SPS) (the electrical current is passed through the sample with 5min reaction time at 350-450°C [83,92]). One important difference among hot-presses is the manipulation of secondary phases; both removal and proportioning are possible, and obviously depends upon the temperature and duration, but also on details of the instrument design and the environment of the ZnSb powder.…”
Section: Thermoelectrics For Power Generation -A Look At Trends In Thmentioning
confidence: 99%